1984
DOI: 10.1111/j.1095-8649.1984.tb04837.x
|View full text |Cite
|
Sign up to set email alerts
|

Diploid gynogenesis induced by hydrostatic pressure in rainbow trout, Salmo gairdneri Richardson

Abstract: Diploid gynogenetic fry of rainbow trout, Salmo guirdnui, were produced by treating eggs activated by UV-irradiated sperm with hydrostatic pressure. Treatments for 10 min at 40 min after activation with 55 000 kPa (8000 psi) pressure resulted in high hatching rates and yields of heterozygous diploid gynogenomes of up to 8 1 Yo. Attempts to produce homozygous diploid gynogenomes by the suppression of the first mitotic division of the eggs failed.Ether treatment alone did not induce diploid gynogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…In many previous studies, it was also reported that tetraploid embryos were successfully induced by the first cleavage inhibition, but they had no survival potential and died soon after hatching or feeding before growing to adult or near-adult size (Lou and Purdom, 1984b;Myers, 1986;Linhart et al, 1991;Arai, 1992;Malison et al, 2001;Sakao et al, 2003). These results suggest that the mortality of tetraploid embryos is not a side effect of the chromosome doubling treatment at the first cleavage, but is the result of the elevation of ploidy status itself, from diploidy to tetraploidy.…”
Section: Mortality Due To Tetraploidymentioning
confidence: 99%
See 1 more Smart Citation
“…In many previous studies, it was also reported that tetraploid embryos were successfully induced by the first cleavage inhibition, but they had no survival potential and died soon after hatching or feeding before growing to adult or near-adult size (Lou and Purdom, 1984b;Myers, 1986;Linhart et al, 1991;Arai, 1992;Malison et al, 2001;Sakao et al, 2003). These results suggest that the mortality of tetraploid embryos is not a side effect of the chromosome doubling treatment at the first cleavage, but is the result of the elevation of ploidy status itself, from diploidy to tetraploidy.…”
Section: Mortality Due To Tetraploidymentioning
confidence: 99%
“…It has been reported that the developmental rate was regulated by the maternal effects such as mitochondrial differences (Robison et al, 1999), egg quality and susceptibility to artificial manipulation (Lou and Purdom, 1984a;Johnstone, 1985;Komen et al, 1991). In this study, the fertilized eggs derived from the same female developed almost synchronously compared to those from the same male, therefore it suggested that the developmental rate should be depending on a maternal effect rather than a paternal one.…”
Section: Factors Affecting the Progression Of The First Cell Cyclementioning
confidence: 99%
“…Survival in control group was 81.09% but survival of triploids was low (46.97%). It has o�en been reported and possibly relates to "egg quality" or to the susceptibility of eggs of different origin to triploidising treatments (Lou and Purdom, 1984;Johnstone, 1985). As MN can occur as a consequence of both structural and numerical chromosomal aberrations (Miller et al, 1998), in this study, the frequencies of micronucleated erythrocytes in a control and heat shocked population of rainbow trout were analysed.…”
Section: Original Papermentioning
confidence: 99%
“…G-C mapping is possible if two of the four strands (halftetrads) from a single meiosis can be recovered (Thorgaard et al 1983). In teleost fish, when eggs are inseminated with UV-irradiated sperm, gynogenetic diploid full-sib progenies representing half-tetrads can be created by preventing release of the second polar body using heat shock, cold shock, or hydrostatic pressure shock techniques (Lou and Purdom 1984;Refstie 1983;Refstie et al 1982). For the maternal parent with a heterozygous genotype at a single gene or codominant marker, heterozygous progenies can be generated if a crossover event occurs between the gene or marker and centromere during meiosis I, while homozygous progenies should be produced when a crossover never occurs.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%